The new knowledge aristocracy: the creative class, mobility and urban growth. (1st January 2007) - Richard Shearmur,
Abstract : Many policy-makers, particularly in North America, have been seduced and influenced by the ideas of Richard Florida, who suggests that cities and regions can be economically revitalised if they make themselves attractive to the mobile and talented 'creative class'. This suggests that economic growth is caused by an influx of such people. This paper argues that it is more plausible to suggest the reverse — that the 'creative class' is attracted to economic growth and that Florida's theories have the unintended consequence of justifying the investment of considerable public resources in support of the lifestyle choices of this already privileged class, in effect sustaining a new knowledge aristocracy at the expense of the immobile majority.